The Effects of Earthworms on Fungal Diversity and Community Structure in Farmland Soil With Returned Straw - Song, Ke; Sun, Yafei; Qin, Qin; Sun, Lijuan; Zheng, Xianqing; Terzaghi, William; Lv, Weiguang; Xue, Yong (Frontiers in Microbiology, 2020)
Background: In order to promote the decomposition of returned straw, reduce the incidence of soil-borne diseases caused by returned straw and accelerate the conversion of straw carbon into soil carbon, we inoculated earthworms into fields with returned straw. This accelerated straw degradation and promoted carbon conversion. However, the impact of the increased earthworm population on the farmland soil ecosystem, especially the structure and function of its microbial community, remains unclear. Methods: We analyzed the effects of straw return and earthworms on the diversity of fungal populations and the community structure of dominant fungal taxa in soil by quantifying fungal population sizes and community compositions via PCR amplification of ITS genes and 18S rRNA gene sequencing.The results showed that earthworm inoculation significantly accelerated the degradation of rice straw and promoted the conversion of straw carbon to soil carbon. Both fungal abundance and α-diversity (Sobs and Shannon index) were higher in the plots with surface straw and without earthworms than those inoculated with earthworms and the controls. PCA analysis indicated that straw return increased the diversity and abundance of, the fungal community whereas earthworms inhibited this expansion of the fungal community caused by straw return. Interestingly, the overall differences in fungal community composition are smallest in plots with straw return, while the dominant fungal community features in plots inoculated with earthworms is closer to the control. Conclusion: Generally, straw return stimulated unclassified_K_fungi, Pseudeurotium and Fusarium with strong cellulolytic ability. In contrast, the abundance of Stachyybotrys, unclassified_c_Sordariomycetes, unclassified_f_Lasiosphaeriaceae and Schizothecium were higher in the plots inoculated with earthworms and in the control. Furthermore, evolutionary analysis showed that the evolution of soil fungal communities tended to diverge after straw return, and the evolutionary directions of fungal species in the plots inoculated with earthworms were similar to the control.